A sustainability analysis of the exploitation of the baru almond (Dipteryx alata Vogel) in the Brazilian Savanna (Sustainability in Debate, 2019)
This article seeks to discuss the results of a survey that sought to identify, by means of indicators and social-economic information, if the exploitation of the baru nut (Dipteryx alata Vogel) - a Brazilian species from the savanna - represents a sustainable alternative to generate income for family farmers in Goias and the Federal District. The results showed that, under the current circumstances, the baru extrativism done by family farmers isn’t a sustainable income generation activity. This result considers the premise that for an activity to be sustainable, it needs to show equilibrium among the various factors of sustainability. The obstacles that the family farmers of the baru nut production chain face may be prejudicial to the proper exploitation of the nut, which could compromise the sustainability of the activity as a whole.